1994
DOI: 10.1084/jem.180.6.2335
|View full text |Cite
|
Sign up to set email alerts
|

Dominant selection of an invariant T cell antigen receptor in response to persistent infection by Epstein-Barr virus.

Abstract: SummaryTo examine T cell receptor (TCR) diversity involved in the memory response to a persistent human pathogen, we determined nucleotide sequences encoding TCR-cx and -/3 chains from HLA-B8-restricted, CD8 + cytotoxic T cell clones specific for an immunodominant epitope (FLRGRAYGL) in Epstein-Barr virus (EBV) nuclear antigen 3. Herein, we show that identical TCR protein sequences are used by dones from each of four healthy unrelated virus carriers; a clone from a fifth varied conservatively at only two resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
246
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(257 citation statements)
references
References 24 publications
10
246
1
Order By: Relevance
“…To identify additional sequence constraints that could predict the functional avidity of Ag recognition of A2/melan-A multimer ϩ CD8 ϩ T cells we compared TCR sequences from A2/melan-A multimer ϩ clones described in this study and recently analyzed TCR sequences of melan-A-specific CTL clones from melanoma patients (23). Within defined V␣-J␣ rearrangements, we found some CDR3␣ sequences (Table III) that were either identical (public sequences) or highly homologous among clones derived from different donors, as previously reported for high affinity T cells selected by chronic exposure to Ag (35,36). In contrast, no public or highly homologous sequences were found in the CDR3␤.…”
Section: Resultsmentioning
confidence: 70%
“…To identify additional sequence constraints that could predict the functional avidity of Ag recognition of A2/melan-A multimer ϩ CD8 ϩ T cells we compared TCR sequences from A2/melan-A multimer ϩ clones described in this study and recently analyzed TCR sequences of melan-A-specific CTL clones from melanoma patients (23). Within defined V␣-J␣ rearrangements, we found some CDR3␣ sequences (Table III) that were either identical (public sequences) or highly homologous among clones derived from different donors, as previously reported for high affinity T cells selected by chronic exposure to Ag (35,36). In contrast, no public or highly homologous sequences were found in the CDR3␤.…”
Section: Resultsmentioning
confidence: 70%
“…3B). It is notable that both the public TCR b-chain and the a-chain used by these clones each includes just three amino acids that are not germline encoded, which helps to explain the recurrence of this common b-chain in unrelated individuals (3,8). For the public TCR b-chain, these were the central proline-X-arginine CDR3 residues where the X position was one of seven different amino acids observed across all the donors (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The residual repertoire of unique TCRs following thymic selection is between 10 and 100 million in humans (1). Despite this vast potential repertoire, immune responses often show strong bias in TCR selection, resulting in immunodominance of certain "public" TCRs that are widely used in individuals with shared MHC types (2)(3)(4)(5). Structural studies have shown that biased TCR usage arises from unique specificity requirements for a given peptide-MHC complex (6,7).…”
mentioning
confidence: 99%
“…The resulting “repertoire” of distinct TCRs expressed in an individual defines a unique footprint of immune protection. Despite this diversity, a significant overlap in the TCR response of different individuals to a variety of antigens and infections has been observed in humans,2, 3, 4 mice,5, 6, 7 and macaques8 (reviewed in 9, 10). This observation led to the notion of a “public” response shared by all, and a complementary “private” response specific to each individual 5.…”
Section: Introductionmentioning
confidence: 99%